2016
DOI: 10.3389/fnhum.2016.00461
|View full text |Cite
|
Sign up to set email alerts
|

Digit Position and Forces Covary during Anticipatory Control of Whole-Hand Manipulation

Abstract: Theoretical perspectives on anticipatory planning of object manipulation have traditionally been informed by studies that have investigated kinematics (hand shaping and digit position) and kinetics (forces) in isolation. This poses limitations on our understanding of the integration of such domains, which have recently been shown to be strongly interdependent. Specifically, recent studies revealed strong covariation of digit position and load force during the loading phase of two-digit grasping. Here, we deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 35 publications
(47 reference statements)
2
19
0
Order By: Relevance
“…For future research it would be interesting to examine expected hardness based on material appearance in relations to grasp force anticipation. The current consensus is that grasp force increases with object weight (Zatsiorsky and Latash, 2008;Marneweck et al, 2016), but less is known to what extend we rely on visual material appearances during force regulations when reaching for objects made of materials that require distinct approach due to their disposition. For instance, what optical characteristics segregate perceived soft objects from perceived hard objects, and do we rely on those characteristics to anticipate the required force to successfully lift the objects?…”
Section: Rated Hardness and Glossinessmentioning
confidence: 99%
“…For future research it would be interesting to examine expected hardness based on material appearance in relations to grasp force anticipation. The current consensus is that grasp force increases with object weight (Zatsiorsky and Latash, 2008;Marneweck et al, 2016), but less is known to what extend we rely on visual material appearances during force regulations when reaching for objects made of materials that require distinct approach due to their disposition. For instance, what optical characteristics segregate perceived soft objects from perceived hard objects, and do we rely on those characteristics to anticipate the required force to successfully lift the objects?…”
Section: Rated Hardness and Glossinessmentioning
confidence: 99%
“…Previous studies have shown similar modulation of forces and placement using three-digit (Albert et al 2009;Fu et al 2011;Fu and Santello 2012) and whole hand (Marneweck et al 2016) grips. Aside from unimanual grasping, manipulation can also be performed with two hands.…”
Section: Introductionmentioning
confidence: 58%
“…As such, in order to understand generalization further, we must first examine the characteristics of both grasp types as they pertain to learned manipulation. The modulation and covariation of effector center of pressure and load forces, for compensatory torque generation, indicates a high-level representation of learned manipulation and this is a general feature for both unimanual and bimanual grasps 2 , 15 , 16 . However, within each grasp type, we have shown certain idiosyncratic characteristics.…”
Section: Discussionmentioning
confidence: 95%
“…Covariation of digit forces-to-placement provides evidence of a high-level representation of learned compensatory torque that drives the flexible coordination where digit forces are selected based on the feedback of digit placement 2 , 14 . Aside from two-digit precision grasping, we have recently shown that digit force-to-placement modulation is a general feature of dexterous manipulation that is also found in whole-hand 15 and bimanual 16 manipulation.…”
Section: Introductionmentioning
confidence: 99%